Association Between Bone Mineral Density and Lipid Profile in Chinese Women - Zhang, Qi (Clin Interv Aging, 2020)
PURPOSE: Atherosclerotic cardiovascular disease may share the risk factors for low bone mineral density (BMD), one of which is dyslipidemia. The association between serum cholesterol and BMD remains controversial. Thus, the correlation between serum lipids and BMD in women was explored in the current study. MATERIALS AND METHODS: This cross-sectional study included 1116 Chinese female participants. Serum samples were collected to evaluate total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and other laboratory markers. Dual-energy X-ray absorptiometry was used to assess lumbar spine, femoral neck, and total hip BMD. RESULTS: In the postmenopausal women, a non-linear relationship was detected between TC, LDL-C, HDL-C, and lumbar spine BMD. Using segmented linear regression, the inflection points were 5.86 mmol/L, 3.52 mmol/L, and 2.37 mmol/L, respectively. To the left of the inflection point, the higher the serum lipid level, the lower the value for lumbar spine BMD. To the right of the inflection point, the higher the serum level of TC and LDL-C, the higher the value for lumbar spine BMD. In the premenopausal women, the association between HDL-C and femoral neck BMD was non-linear. In addition, LDL-C had a positive association with BMD of the femoral neck and HDL-C had an inverse association with BMD of the femoral neck in postmenopausal women. CONCLUSION: In postmenopausal women, the relationship between TC, LDL-C, HDL-C, and lumbar spine BMD was non-linear. TC, LDL-C, and HDL-C were negatively associated with lumbar spine BMD when the values were less than 5.86 mmol/L, 3.52 mmol/L, and 2.37 mmol/L, respectively. The mechanisms of the association were unclear, and further research is warranted to clarify the relationship.